Empatia judicial: uma proposta compatibilista - Rosario, Marcelle Coelho do (Universidade do Vale do Rio dos Sinos, 2015)
The Judicial Empathy includes today the set of most debated topics recently. American President Barack Obama was an exponent contributor so this discussion could reach its pinnacle. His statements expressing the wish that the American judiciary would be composed of empathetic judges, caused unrest in the political, legal and social environments. The participation of empathy in the judicial decision-making process has been discussed whatever the chosen strand. Scientific and non-scientific studies compete with countless empathy conceptualizations, as well as multiple understandings about its usage in the judicial process to be, or not, desirable and moral. So far, there is no consensus on the subject. But what empathy concept those discussions are being referred to? Is empathy an emotion or not? Once defined this concept, would it be applicable to all judicial needs? Thus, the use of judicial empathy necessarily compromising the legal and moral duties of impartiality of the judiciary? The judicial empathy applies a bias to the decisions? Judicial decisions must be justified only by laws? To those who answer yes to the previous question, how to treat the so-called hard cases, that emerge from the contemporary society and that are not yet contemplated in the legislation? Thus, this research aims to answer the above mentioned formulations. The researched hypothesis is empathy as an essential tool to the judicial decision-making process, judicial empathy. This work will defend the empathy as desirable to the judicial decision-making process, however not belonging to the group of emotions (though the emotions are elements of this process), but as a cognitive skill, and the impartiality of magistrate as the result of judicial empathy. Were used as background paper the works Against Empathy and Is Empathy necessary for morality? by Jesse Prinz, who offers an extensive argument against judicial empathy; In defense of judicial empathy, by Thomas M. Colby which executes a brilliant defense, and Paradoxos e ambiguidades da imparcialidade da judicial: entre "quereres" e "poderes", by Bárbara G. L. Baptista, the national impartiality bible.
Keywords: Conceito de empatia; Empatia judicial; Imparcialidade; Concept of empathy; Judicial empathy; Impartiality; ACCNPQ::Ciências Humanas::Filosofia